(untitled) (Entrepreneurship Journal for Finance and Business, 2023)
The research aims to study and analyze the philosophy behind the technique Time Driven Activity Based Budgeting (TDABB) and its reflection in achieving cost reduction through application in the Kufa Cement Factory of the Iraqi Ministry of Industry. After studying the reality of the Kufa Cement Factory and applying the technique Time Driven Activity Based Budgeting depending on the data obtained through field visits and personal interviews with officials and workers as well as data extracted from the factory records (the research sample), the research reached several conclusions, the most important of which are: There is a significant impact of the technique Time Driven Activity Based Budgeting in achieving objectivity in terms of cost determination, it represents a means that helps manage cost in light of future developments in terms of its ability to track and detect non-value-adding activities for the purpose of canceling/reducing/replacing them. As for the most important recommendations, they were: The importance of cost reports for the various parties in the economic unit, so they should contain appropriate information for making right decisions and developing them in light of future opportunities and challenges through the adoption of technique Time Driven Activity Based Budgeting, as it is more able to reflect the actual consumption of resources by the departments. Productivity.